Some Aspects of Larval Nutrition of the Freshwater Prawn, Macrobrachium Rosenbergii (De Man) with an Emphasis on Lipid Metabolism - Roustaian, Paymon (1999)
Changes in biochemical composition and fatty acid metabolism during larval development of the freshwater prawn, Macrobrachium rosenbergii (de Man) were studied to enhance the current understanding of the physiology and nutritional requirements of the growing larvae. Protein was always the major organic constituent followed by lipids and then carbohydrates. Protein concentration increased during development of both fed and starved larvae, suggesting its important role in morphogenesis. The decline of lipid during the larval development was more rapid for starved larvae which suggests a probable utilisation of lipid as metabolic source of energy. Low levels of carbohydrates in both fed and starved larvae may indicate their limited role in larval metabolism. The amino acid composition appeared to be relatively unchanged during the larval growth, suggesting that the amino acids requirement of the freshwater prawn is relatively constant during larval life. Unlike amino acids, fatty acids revealed much wider range of variation during larval development. Although a decrease in total saturated fatty acid and monounsaturated fatty acids was observed, polyunsaturated fatty acids tended to increase during larval development. M. rosenbergii larvae appeared to have capability to sufficiently converrpalmitic (16:0), linoleic (l8:2n-6) and linolenic (18:3n-3) acids to stearic (18:0), arachidonic (20:4n-6) and ecosapentaenoic (20:5n-3) acids, respectively. Findings revealed that dietary lipid level of > 15% (dry weight) has detrimental effects on the larval growth and survival. The best performance in terms of postlarval production, dry weight, protein and lipid depositions were observed for the diet containing 12% lipid. The lack of suitability of diets rich in saturated fatty acids for larval freshwater prawn was noted. Despite a wide variation in the dietary saturated to polyunsaturated fatty acid ratio, larvae revealed a narrow range indicative of the importance of such ratio in the larval metabolism. Moreover, regardless of the significant dietary variations in n-3 to n-6 ratios, the larval n-3 to n-6 ratios were remarkably similar, indicating the importance of such ratio in the larval fatty acid metabolism. The incorporation of linseed oil (as a source of linolenic (18:3n-3) acid) at 25 to 75% of supplemented oil increased postlarval production, while larvae fed with linseed oil at 100% revealed significantly lower postlarval production. Although larval tissue level of arachidonic (20:4n-6) acid was not significantly affected by the dietary level of n-3 or n-6 fatty acids, biosynthesis, of eicosapentaenoic (20:5n-3) acid is most likely affected.